Body language in elite soccer: comparing tactical and emotional nonverbal expressions using different video sources for investigation - Lian, I.; Gjesdal, S.; Jordet, G. (International Journal of Sport and Exercise Psychology, 2026)
The aim of this study was to explore elite-level soccer players` use of nonverbal behaviour (NVB) during real matches and compare different video sources (i.e., tactical, broadcast, and close-up) in terms of investigating this topic. The NVBs of eight elite players representing their national team (and a top-5 European league team) were analysed during one game. NVB was divided into tactical and emotional categories. Two Wilcoxon tests were performed. The results indicate that players displayed significantly more tactical NVB (Median = 146) than emotional NVB (Median = 52.50), Z = -2.52, p = .012, r = .89 but that they did not differ significantly in terms of positive and negative emotional NVB. Furthermore, there were more registrations of NVB captured from the close-up view videos as compared to both the tactical view (77.5% of the close-up view) and broadcast view (38.4% of the close-up view). Specifically, a statistically significant difference was found between close-up view and broadcast view, but not between close-up view and tactical view for most of the NVB categories. The findings demonstrate how players differ in their displays of tactical and emotional NVB, as well as how different video sources enable us to capture different amounts of NVB.